Advancing to the era of cancer immunotherapy. Issue 9 (24th June 2021) - Wang, Yun; Wang, Min; Wu, Hao‐Xiang; Xu, Rui‐Hua
Abstract: Cancer greatly affects the quality of life of humans worldwide and the number of patients suffering from it is continuously increasing. Over the last century, numerous treatments have been developed to improve the survival of cancer patients but substantial progress still needs to be made before cancer can be truly cured. In recent years, antitumor immunity has become the most debated topic in cancer research and the booming development of immunotherapy has led to a new epoch in cancer therapy. In this review, we describe the relationships between tumors and the immune system, and the rise of immunotherapy. Then, we summarize the characteristics of tumor‐associated immunity and immunotherapeutic strategies with various molecular mechanisms by showing the typical immune molecules whose antibodies are broadly used in the clinic and those that are still under investigation. We also discuss important elements from individual cells to the whole human body, including cellular mutations and modulation, metabolic reprogramming, the microbiome, and the immune contexture. In addition, we also present new observations and technical advancements of both diagnostic and therapeutic methods aimed at cancer immunotherapy. Lastly, we discuss the controversies and challenges that negatively impact patient outcomes. Abstract : In this review, we present a clear view of the major factors and regulators associated with cancer immunotherapy and to provide our point of view on the latest available technologies and treatment methods for resolving clinical problems.